2021
DOI: 10.13189/ujaf.2021.090420
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Bank's Wealth: How is Islamic Banks's Financial Performance Affected by Asset Quality and Operational Efficiency

Abstract: Islamic banks are recognised as entities which support social objectives as well as economic development of the country. Financial performance of the global Islamic banking and finance has shown promising growth as equal to well-established conventional banks. The study aims to investigate the effect of asset quality and operational efficiency on the financial performance of Islamic banks in Malaysia. The study uses panel data analysis, whereby the annual reports of 16 Islamic banks in Malaysia are analysed ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…The greater the value, the more stable the banking system is. In our study, we measure operating efficiency as proxied by the non-interest expense ratio suggested by Ali, Shuib and Nor (2021), Dutta and Saha (2021), Rahman et al (2021) and Supiyadi (2021) which is calculated as a non-interest expense to the total asset. So, we may claim that increased operational efficiency improves the financial sector's stability.…”
Section: Methodsmentioning
confidence: 99%
“…The greater the value, the more stable the banking system is. In our study, we measure operating efficiency as proxied by the non-interest expense ratio suggested by Ali, Shuib and Nor (2021), Dutta and Saha (2021), Rahman et al (2021) and Supiyadi (2021) which is calculated as a non-interest expense to the total asset. So, we may claim that increased operational efficiency improves the financial sector's stability.…”
Section: Methodsmentioning
confidence: 99%
“…Kinerja Dalam mengoprasionalkan bisnis modal menjadi faktor utama pendukung. Dalam mengantisipasi adanya kerugian kecukupan modal diperlukan setiap perseroan [3]. Penilaian permodalan yaitu nilai pada kecukupan modal bank dalam mengcover risiko kini serta dijadikan antsipasi dimasa yang akan datang.…”
Section: Pendahuluanunclassified
“…This has led to the growth of the most domestic market shares of Islamic banks all over the world, including Malaysia. Currently, Malaysian Islamic banks accumulated approximately USD195.6 billion of global Islamic banking assets in 2019 (Ali et al, 2021). The Islamic banking industry in Malaysia has been acknowledged as one of the international Islamic Financial Institutions (IFIs) ever since its financial performance began showing remarkable improvements year by year.…”
Section: Introductionmentioning
confidence: 99%